Determinants of FDI flows within emerging economies : a case study of Poland - Mironko, Arkadiusz; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This study provides a detailed examination of foreign direct investment (FDI) in Poland and explores the impact this has on foreign investment policy. It analyzes and identifies location patterns of FDI and strives to determine the supporting motives behind location choices of foreign companies.
Keywords: Investments, Foreign -- Poland; Industries -- Poland; Poland -- Economic conditions